Breast cancer characteristics and surgery among women with Li‐Fraumeni syndrome in Germany—A retrospective cohort study. (26th September 2021) - Rippinger, Nathalie; Fischer, Christine; Sinn, Hans‐Peter; Dikow, Nicola; Sutter, Christian; Rhiem, Kerstin; Grill, Sabine; Cremer, Friedrich W.; Nguyen, Huu P.; Ditsch, Nina; Kast, Karin; Hettmer, Simone; et al.
Abstract: Background: Women with Li‐Fraumeni syndrome (LFS) have elevated breast cancer (BC) risk. Optimal BC treatment strategies in this population are yet unknown. Methods: BC subtypes and treatment were retrospectively investigated between December 2016 and January 2019 in a multicentre study. BC risks were evaluated according to the type of surgery. Results: Thirty‐five women of our study population (35/44; 79.5%) had developed 36 breast lesions at first diagnosis at a mean age of 34 years. Those breast lesions comprised 32 invasive BCs (89%), three ductal carcinoma in situ alone (8%) and one malignant phyllodes tumour (3%). BCs were mainly high‐grade (18/32), of no special type (NST; 31/32), HER2‐enriched (11/32) or luminal‐B‐(like)‐type (10/32). Affected women ( n = 35) received breast‐conserving surgery (BCS, n = 17) or a mastectomy (ME, n = 18) including seven women with simultaneous contralateral prophylactic mastectomy (CPM) at first diagnosis. Nineteen women suffered 20 breast or locoregional axillary lesions at second diagnosis with mean age of 36. Median time between first and second diagnosis was 57 months; median time to contra‐ and ipsilateral recurrence depended on surgical strategies (BCS: 46 vs. unilateral ME: 93 vs. bilateral ME > 140 months). Women with a primary treatment of solitaire therapeutic ME suffered from contralateral BC earlier compared to those with therapeutic ME and CPM (median: 93 vs. >140 months). Conclusion: Aggressive BC subtypes occur among women with LFS. Surgical treatment, i.e. ME and CPM, may prolong time to a second BC diagnosis. Conclusion on long‐term survival benefit is pending. Individual competing tumour risks and long‐term outcomes need to be taken into consideration. Abstract : Women with Li‐Fraumeni Syndrome face challenging breast cancer risks. Therapeutic or contralateral prophylactic mastectomy can be associated with a prolonged median time to develop contralateral breast cancer.